1‐Sarcosine–angiotensin II infusion effects on food intake, weight loss, energy expenditure, and skeletal muscle UCP3 gene expression in a rat model. Issue 3 (11th March 2014) - Cichello, S. A.; Weisinger, R. S.; Schuijers, J.; Jois, M.
Abstract : Background: There are a myriad of proteins responsible for modulation of expenditure of energy. Angiotensin II (Ang II) is a vital component of renin‐angiotensin system that affects blood pressure and also linked to both cachexia and obesity via fat and muscle metabolism. Previous research suggests that the direct action of Ang II is on the brain, via angiotensin II type 1 receptor protein, affecting food intake and energy expenditure. The objective of the study is to investigate the effect of 1‐sarcosine (SAR)‐Ang II infusion on energy expenditure and metabolism in a rat model of congestive heart failure cachexia. Methods: Adult female rats of the Sprague Dawley strain ( n  = 33) were used (11 pair‐fed control, 12 ad libitum and 10, 1‐sarcosine–angiotensin II‐infused rats). Body weight, faecal excretion, feed intake (in grams), water intake (in milliliters) and urine excreted were recorded daily. The measurements were recorded in three different periods (4 days prior to surgery, "pre‐infusion"; day of surgery and 5 days postsurgery, "infusion period"; days 7 to 14, "recovery" period). Different analytical methods were used to measure energy expenditure per period, uncoupling protein 3 mRNA expression, crude protein and adipose tissue body composition. Results: During the infusion period, the SAR–Ang II group experienced rapid weight loss ( p  < 0.05) in comparison to the ad libitum and pair‐fed groups. The SAR–Ang II group displayed lower ( p  < 0.05) body fat content (in percent) than the controls. There was also increased ( p  < 0.05) uncoupling protein 3 (UCP3) mRNA expression in the SAR–Ang II group and pair‐fed group when compared to the controls. Conclusion: In summary, the results suggest that SAR–Ang II infusion impairs appetite and decreases body weight by wasting predominantly adipose tissue, which may be due to elevated energy expenditure via mitochondrial uncoupling (UCP3 protein activity).